Assessing land suitability for aquifer storage and recharge in northern Ghana using remote sensing and GIS multi-criteria decision analysis technique - Owusu, Seth; Mul, Marloes L.; Ghansah, Benjamin; Osei-Owusu, P.K.; Awotwe-Pratt, V.; Kadyampakeni, D. (Springer, 2017)
Increasing climate variability and challenge in access to water pose major impediments to rainfed agricultural productivity. Extensive flooding of agricultural lands during the rainy season and lack of water during the 8-month long dry season affect the livelihood of the people in the northern Ghana, a situation that calls for better water management practices. The use of aquifer storage and recharge (ASR) based technique, helps to reduce flooding and improve access to water during the dry season; however such technology has specific requirements for successful implementation. This study assesses suitable areas for the technology in the northern Ghana terrain using multi criteria decision analysis (MCDA) in ArcGIS environment. The result suggests around 66% (48,516 km2) of the crop area in the northern Ghana available for the technology are within moderate to very high suitable sites, of which 44% (29,490 km2) fall into the high and very high suitable sites. This could imply high potential for the artificial groundwater storage system in northern Ghana given other conditions.